Communication and evaluation processes for extension projects: Dialogues between the university and society (Research, Society and Development, 2026)
This article analyzes the communication and evaluation processes of university extension at the Federal University, focusing on the interaction between the academic environment and society. The objective is to discuss how the dissemination of extension results and evaluation mechanisms influence the social perception of university impact. The methodology adopted is qualitative and exploratory, utilizing documentary analysis of regulatory frameworks and semi-structured interviews with extension managers and coordinators from various fields of knowledge. The results indicate that, although formal communication channels exist (websites and social media), there are significant flaws in data updating and the effectiveness of outreach to the external public, who often do not access institutional digital media. A predominance of research metrics over extension was identified, which discourages the systematization of results. It is concluded that extension communication must be guided by dialogical interactivity, going beyond the mere transfer of information. The study proposes the adoption of open data platforms and the inclusion of external actors in the evaluation process, ensuring that extension fulfills its role as a two-way street and promotes transparency and the strengthening of the bond between the university and the community.